2018
DOI: 10.3311/ppme.12117
|View full text |Cite
|
Sign up to set email alerts
|

Grey Relational Analysis and Anova to Determine the Optimum Process Parameters for Friction Stir Welding of Ti and Mg Alloys

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…GRG may be classified into particularly; Smaller the better, Larger the better, or Nominal could be a better (NB) criterion. The preferred quality characteristics for Final Maximum interface temperature, equivalent Von-Mises stress, and total deformation are Smaller the better criterion, and then it’s expressed by using equation 24 :…”
Section: Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…GRG may be classified into particularly; Smaller the better, Larger the better, or Nominal could be a better (NB) criterion. The preferred quality characteristics for Final Maximum interface temperature, equivalent Von-Mises stress, and total deformation are Smaller the better criterion, and then it’s expressed by using equation 24 :…”
Section: Methods Of Analysismentioning
confidence: 99%
“…of factors; y i ( k ) = original sequence; y i *( k ) value after Grey relational generation; min y i ( k ) and max y i ( k ) are the minimum and maximum value of y i ( k ), respectively. The calculation for Grey relation coefficient was done using equation 24 :…”
Section: Methods Of Analysismentioning
confidence: 99%
“…GRA depends on grey-system theory, suitable for solving problems with intricate relationship between several factors and levels. Therefore, GRA reduces intricacy and can be used for solving various types of multi-attribute decision-making problems [11,12]. In a similar way TOPSIS-approach is also a simple and effective method for multi-attribute decision making problems used in several applications mainly in selecting the process-parameters in manufacturing studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sivam et al [14] applied Grey relational analysis and ANOVA in multi response optimization of setting input variable for getting better product quality in machining of magnesium AM60, the expected response and measured response are fairly close in the study. Sivam et al [15] also studied the friction stir welding of Ti and Mg alloys by using Taguchi method, Grey relational analysis and ANOVA approaches to determine the optimum process parameters. Their results showed that the measured values are close to the expected values.…”
Section: Introductionmentioning
confidence: 99%